Showdown in the rockies - Tailer, Kathleen (Love inspired suspense., 2024)
A secret cartel operation in the wilderness. A perilous winter pursuit. When their helicopter is shot out of the sky after they discover a drug operation, Detective Flynn Denning—along with her nephew and her ex-boyfriend Derek King—is stranded in the unforgiving Colorado mountains. They’ll need to rely on Derek’s military skills to survive the treacherous conditions and the assailants on their trail. But with the cartel dead set on eliminating any witnesses to their operation, this mission might be their last…